(untitled) (Nexus International Journal of Science and Education, 2024)
The current study evaluates whether compassionate classroom behavior is the relationship between teachers’ reciprocating teaching approach and students’ technical-vocational livelihood skills. In this study, the researcher selected 350 junior high school students who were respondents and were taken from cluster 6 public secondary schools in Davao City Division. A random sampling technique was utilized to select the respondents. A non-experimental quantitative research design using a descriptive-correlational method was employed. The data collected were subjected to the following statistical tools: Mean, Pearson Moment Product Correlation, multiple linear regression analysis, and Structural Equation Model through Mediation Analysis. Findings revealed that teachers’ reciprocating teaching approach, students’ technical-vocational livelihood skills, and compassionate classroom behavior in cluster 6 public secondary schools in Davao City were described as extensive. Further, correlation analysis demonstrated a significant relationship between teachers’ reciprocating teaching approach, students’ technical-vocational livelihood skills, and compassionate classroom behavior in cluster 6 public secondary schools in Davao City. The Structural Equation Model through Mediation Analysis proved that compassionate classroom behavior partially mediated the relationship between teachers’ reciprocating teaching approach and students’ technical-vocational livelihood skills.